Optimization of tool geometry design: the effects on surface roughness - Mohammad, Rosdi; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah; Mustapha, Faizal; Aoyama, Hideki (Malaysian Tribology Society, 2016)
This paper aims to optimize a new cutter design for turning of AISI12L14 with TiAlN-coated tungsten carbide tool. The interaction of the tool geometry and work-piece on the performance characteristic of surface roughness has been investigated, and Taguchi method is selected as the technique for the optimization. Results showed that gradually altering negative to positive rake angles will give significant influence on part’s surface finishing. However, the minor cutting tool edge, Kr2 with 3° is found to be the predominant factor in influencing surface roughness, Ry. Taguchi parameter design was found to be a simple, systematic, reliable, and efficient tools for the tool’s optimization process in turning of AISI 12L14.